Emergency Department Healthcare Providers' Knowledge of Ischemic Stroke - Sangeeta Lamba; Tiffany Murano; Roxanne Nagurka (Tabriz University of Medical Sciences, 2013)
Introduction: Stroke is one of the leading causes of death and disability in the United States. Nationally, only 3-8% of patients with Acute Ischemic Stroke (AIS) who are eligible for thrombolysis currently receive recombinant tissue plasminogen factor (r-TPA). Lack of knowledge and familiarity with thrombolytics in stroke therapy are major impediments. We investigated the baseline stroke management concepts and knowledge of AIS therapy in Emergency Department (ED) healthcare providers and then assessed the impact of a brief educational intervention. Method: An anonymous 14-item (11 multiple choice and 3 open-ended) questionnaire was administered to a convenience sample of 58 healthcare providers in the ED of a Level-1, tertiary care, academic, urban hospital. The survey was collected and a 15-minute lecture was provided to the group. A post-test was administered immediately and six months after the intervention. Data collected were analyzed with chi-square, analysis of variance and Kruskal-Wallis analysis using SAS 9.1.3. Results: Of the 58 respondents 77% (45/58) identified r-TPA as the thrombolytic agent, but only 56% (33/58) knew the therapeutic window and 29% (17/58) knew the "Door-to-CT" time. Sixty-two percent (36/58) of the respondents reported unfamiliarity with the National Institute of Health's Stroke Scale and the eligibility criteria of r-TPA. Median score pre-education was 5/14 which improved to 11/14 (CI 8-12, p<0.0001) and six months later was 8/14 (best score was 12, p<0.0001). Only 8% (5/58) of the respondents expressed a special interest in stroke. Conclusion: Few medical personnel express a special interest in stroke and many misunderstand basic management concepts as well as eligibility criteria for thrombolysis in AIS. A brief targeted intervention improves knowledge and familiarizes ED healthcare providers about the use of r-TPA in AIS. Improvement in knowledge was demonstrated on testing immediately and at six month follow-up.